MODEL KOMUNIAKSI KONTEKSTUAL PUSTAKAWAN DAN PENGUNJUNG DALAM MENUNJANG LAYANAN SIRKULASI PADA BADAN PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI SULAWESI TENGGARA - rosmin rosmin (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
ABSTRACT The principal issues raised in this research is how Contextual Communication Model and Visitor Librarian in Supporting Services Circulation. The purpose of this research was to determine and describe the Contextual Communication Model and Visitor Librarian Circulation Services to Support the library and archives southeast Sulawesi region. In this study, the authors used the descriptive research to describe the facts and the properties of the relationship between the phenomenon investigated. With the qualitative methods to understand the phenomenon of what is experienced by the subject of research by describing and collect data through literature and field by interview and observation with 12 informants as a data source. The results showed that the implementation of the Capital Communications Contextual Librarian and visitors to Support Services Circulation of the library and archives area in Southeast Sulawesi in principle is already well underway ranging from Media communication and interest in reading run optimally because it is supported by adequate funding so that the Support Services circulation only through donations and so it was appropriate interest in reading that is expected to users / pemustaka. While the source obtained from the collection development Willingness or Hiba. Keywords: Communication Librarian